Comparison of Aggression among Madrassa, School and College Students: A Case Study of Sialkot District (Journal of Social Sciences Review, 2025)
The current study was conducted to compare the aggression among students from three distinct educational settings in Sialkot, Pakistan: madrassas, schools and colleges. Cross-sectional research design was used in the study. Sample was selected from schools, madrassas and colleges of Sialkot through stratified sampling technique. Sample size was determined after getting the sampling frame of target population. Sample of 500 students, 100 from madrassa, 200 from school and 200 from colleges participated in the study. Respondents were between the age ranges of 13 to 19 years. Aggression was measured by using the Aggression Scale for Adolescents (Zaqia, & Shehzadi, 2019). Results of t-test analysis showed a significant difference in aggression between males and females (r =.007, p < 0.01). Male (M=27.48) reported higher on aggression than females (M=24.91). The ANOVA revealed that aggression was found significantly lower among madrassa students (M=21.77), as compared to school (M=26.29) and college student (M=28.68). Teachers, school counselors, and legislators can use the study's practical implications to create intervention programs that address emotional control, violence prevention, and mental health assistance in Pakistan's diverse educational environments.
Keywords: Madrassas; Aggression; Colleges; Stratified Sampling; Schools